2019
DOI: 10.1108/et-02-2019-0041
|View full text |Cite
|
Sign up to set email alerts
|

Apprenticeship for craftspeople in the construction industry: a state-of-the-art review

Abstract: Purpose Apprenticeship programmes are designed to provide young trainees with essential broad-based skills. Through apprenticeships, different sectors that are underpopulated can fill up their skills gaps. Apprenticeships are particularly useful to the construction sector which has a high ageing workforce and associated lower labour productivity. However, the completion rates of apprenticeship training programmes in the construction sector remain low in several countries across the globe. Thus, the purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 90 publications
4
23
0
Order By: Relevance
“…These studies can be classified into three groups: pre-training, training and post-training. For instance, the factors influencing career choice among female trainees is a pre-training issue (Haworth et al, 1986), whereas a low completion rate is a training issue (Daniel et al, 2020). However, the review of existing literature reported in Daniel et al (2020) indicates that very little attention has been paid to apprenticeships in developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…These studies can be classified into three groups: pre-training, training and post-training. For instance, the factors influencing career choice among female trainees is a pre-training issue (Haworth et al, 1986), whereas a low completion rate is a training issue (Daniel et al, 2020). However, the review of existing literature reported in Daniel et al (2020) indicates that very little attention has been paid to apprenticeships in developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…Systematic literature review (SLR) is a well-established approach used to distil built environment research. For instance, SLR has been applied to construction output modelling (Oshodi et al, 2020), construction craftspeople apprenticeship (Daniel et al, 2020) and off-site construction (Mostafa et al, 2016), among others. Although several methods have been used to review the literature (such as critical review and narrative review), 'replicability' and 'rigour' are some of the advantages of utilising SLR.…”
Section: Methodsmentioning
confidence: 99%
“…A HE provider’s main objective is to produce work-ready learners who have a holistic understanding upon completing their academic experience (Daniel et al , 2019). Thus, the pedagogical approach needs to focus on the application of knowledge effectively through holistic understanding.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recent studies indicate that there need to be learning opportunities catered explicitly in developing the student experience, especially in the built environment (BE) sector (Fernández-Caramés and Fraga-Lamas, 2019; Diao and Shih, 2019). BE courses heavily rely on various students from different backgrounds and exposure levels, seeking an equal opportunity for learning and academic progression (Daniel et al , 2019). Thus, concepts of additional learning opportunities need to be identified, adopted and presented to the current context of learning in HE within the BE sector.…”
Section: Introductionmentioning
confidence: 99%